2014
DOI: 10.1155/2014/409021
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Mouse Embryonic Stem Cells and Induced Pluripotent Stem Cells to Chimeras through Injection and Coculture of Embryos

Abstract: Blastocyst injection and morula aggregation are commonly used to evaluate stem cell pluripotency based on chimeric contribution of the stem cells. To assess the protocols for generating chimeras from stem cells, 8-cell mouse embryos were either injected or cocultured with mouse embryonic stem cells and induced pluripotent stem cells, respectively. Although a significantly higher chimera rate resulted from blastocyst injection, the highest germline contribution resulted from injection of 8-cell embryos with emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…In addition, we found that IL-10 levels were not different between time points or groups. Guo et al found a similar result in a rat model of acute pancreatitis [ 39 ]. This suggests that TEAS may play a critical role in anti-inflammation through reducing the levels of proinflammatory cytokines in the plasma but may not have much influence on anti-inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 52%
“…In addition, we found that IL-10 levels were not different between time points or groups. Guo et al found a similar result in a rat model of acute pancreatitis [ 39 ]. This suggests that TEAS may play a critical role in anti-inflammation through reducing the levels of proinflammatory cytokines in the plasma but may not have much influence on anti-inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 52%
“…Earlier experiments in the field of cell reprogramming demonstrate that changes of the differentiation level in specialized epidermal cells can be achieved by nuclear transfer or under the influence of four specific genes regulating cell pluripotency [2,4,18]. There is evidence that induced pluripotent dermal fibroblast can be involved in the formation of teratomas in timusfree mouse [23] and defrosted GFP-MEFs derived iPSCs can participate in organ structures and the tissue building of chimera mouse [24]. Other research demonstrates substantial differences between adult stem-like cells and ESCs after the separation of mixed cell culture into GFP+/GFP-cell populations by flow cytometry and/or using mixed embryonic bodies to transfer under kidney capsules to create teratomes [22].…”
Section: Discussionmentioning
confidence: 99%
“…Previous basic research revealed that dermal macroenvironment is important in the maintenance of bulb cell population and hair follicle growth [21,22]. Based on findings that demonstrate the plasticity as well as regenerative and inductive properties of hair follicle dermal cells [23,24], we have postulated that their epigenetic can be changed under the influence of an embryonic microenvironment when DPCs are injected into the cavity of an expanded blastocyst. They may multiply and contribute to organs and tissue of mosaic animal models after transferring microinjected embryos to foster mothers.…”
Section: Introductionmentioning
confidence: 99%
“…Although the aggregation method requires less equipment and is easier to operate, it has the disadvantage that the embryo development stages that can be used are limited. Both methods have been widely used to generate transgenic mice, and differences in the generation and germ‐line transmission efficiency have been reported for each method . It was reported that the germ‐line transmission efficiency of chimeric animals increased by using 8‐cell embryos.…”
Section: Introductionmentioning
confidence: 99%
“…Both methods have been widely used to generate transgenic mice, and differences in the generation and germ-line transmission efficiency have been reported for each method. 17 It was reported that the germ-line transmission efficiency of chimeric animals increased by using 8-cell embryos.…”
mentioning
confidence: 99%